Sport commitment among competitive female gymnasts: A developmental perspective - Weiss, W. M.; Weiss, M. R. (Research Quarterly for Exercise and Sport, 2007)
The purpose of this study was to examine age and competitive level differences in the relationship between determinants and level of sport commitment. Gymnasts (N = 304) comprised three age groups (8-11, 11-14.5, and 14.5-18 years) and two competitive levels (Levels 5-6 and 8-10). Multiple regression analyses revealed: (a) perceived costs and social constraints from parents and best friends were the strongest predictors of commitment for the youngest gymnasts, (b) perceived costs, personal investments, and parent social constraints predicted commitment for 11-14.5-year-old gymnasts, and (c) perceived competence and costs predicted commitment for the oldest gymnasts. Competitive level differences also emerged; for Level 5-6 gymnasts, personal investments, perceived costs, coach social support, and social constraints by coach, best friend, and teammates were predictors of commitment. Personal investments and teammate social constraints were significant predictors for Level 8-10 gymnasts. Developmental factors and additional determinants are important to consider in further studies of the sport commitment model.